The effect of free cash flow and leverage on earnings management: Moderating role of good corporate governance - Santoso, Aprih (Asian Management and Business Review, 2023)
The purpose of this study is to provide empirical evidence on the impact of free cash flow and leverage on revenue management moderated by the variable of good corporate governance. The research sample consisted of 200 data samples drawn from 20 sub-sectors of the company's consumer products on 2011-2020. The sampling technique used was intentional sampling. Data were analyzed by Moderate Regression Analysis (MRA). The testing results show that free cash flow has a significant negative impact on earnings management, leverage has no impact on earnings management, good corporate governance can mitigate free cash flow, and lastly good corporate governance has a negative impact on earnings management. It shows that the effects of leverage cannot be mitigated. Discussion of the findings that are not in accordance with the initial hypothesis is explained in the final section and the implications of this article.